Effect of molecular distillation on the anti-inflammatory activity and neurotoxicity of Asarum essential oil - Liu, Yang; Wang, Fang; Guo, HuiWen; Zhang, Dingkun; Zhang, Xiaofei; Wu, Zhenfeng; Li, Huiting; Xian, Yang; Yue, Pengfei; Yang, Ming (Frontiers in Pharmacology, 2023)
Asarum essential oil (AEO) has been shown to have good pharmacological activities for the anti-inflammatory and analgesic effects, but increasing the dose may cause toxicity. Therefore, we studied the toxic and pharmacodynamic components of AEO by molecular distillation (MD). Anti-inflammatory activity was assessed using RAW264.7 cells. Neurotoxicity was assessed in PC12 cells and the overall toxicity of AEO was evaluated in the mouse acute toxicity assay. The results showed that AEO is primarily composed of safrole, methyl eugenol, and 3,5-dimethoxytoluene. After MD, three fractions were obtained and contained different proportions of volatile compounds relative to the original oil. The heavy fraction had high concentrations of safrole and methyl eugenol, while the light fraction contained high concentrations of α-pinene and β- pinene. The original oil and all three fractions exhibited anti-inflammatory effects, but the light fraction demonstrated more excellent anti-inflammatory activity than the other fractions. Asarum virgin oil and MD products are all neurotoxic. The exposure of PC12 cells to high concentrations of AEO resulted in abnormal nuclei, an increased number of apoptotic cells, increased ROS formation, and decreased SOD levels. Moreover, the results of acute toxicity tests in mice revealed that the light fractions were less toxic than virgin oils and other fractions. In summary, the data suggest that the MD technology enables the enrichment and separation of essential oil components and contributes to the selection of safe concentrations of AEO.